Auditoría Tributaria en la empresa ADECAMOR Cía. Ltda., período 2021. - García Sisa, Lizbeth Anahí (2023)
TAX AUDIT IN THE COMPANY ADECAMOR CÍA. LTDA., PERIOD 2021 The current research project, titled "Tax Audit in the Company ADECAMOR C. Ltd., Period 2021," has been carried out to assess whether the taxpayer is correctly complying with their tax obligations with the tax authorities and to reduce risks that could later negatively affect the company. The entire process has been carried out in accordance with the Internal Tax Regime Law and its regulations, as well as other related regulations. The research work is distributed in five chapters as follows: Reference framework, theoretical framework, methodological framework, results and discussion, conclusions and recommendations. During the development of the Tax Audit, several techniques and instruments were applied with the purpose of verifying and determining that the processes, accounting operations and tax obligations of the taxpayer have been adequately complied with. For this purpose, information provided by the entity was analyzed, such as documents, forms, annexes and accounting records, in order to find possible findings, omissions, errors and inconsistencies. In turn, the same documentation serves as support to justify the accounting operations during fiscal year 2021. Finally, the results were presented, where the tax and economic situation of the company can be determined, and based on this, the respective conclusions and recommendations are issued. These will contribute to solve certain deficiencies, so that in the future better results are obtained in terms of tax processes.